Water and cellulose stable isotopes in northern Patagonia - Tiphaine Penchenat; Françoise Vimeux; Valérie Daux; Olivier Cattani; Maximiliano Viale; Ricardo Villalba; Ana Srur; Clément Outrequin (PANGAEA, 2020)
The data set contains 5-min resolution meteorological data (temperature and relative humidity), 5-min resolution isotopic composition of water vapor, isotopic composition of precipitation for 11 rain events, isotopic composition of 10 river samples, isotopic composition of 6 leaf water samples and isotopic composition of 5 cellulose samples. The data are in February and March 2017. The site location is 41°47.412 extquotesingleS, 71°34.355 extquotesingleW, 1175 m.